PENGEMBANGAN PARIWISATA EKONOMI KREATIF DALAM PENINGKATAN PAD BERBASIS PARTISIPASI MASYARAKAT LOKAL DI KABUPATEN KONAWE SELATAN - Genggong, Marsia Sumule; Latif, Abdul; Ashmarita, Ashmarita; Makmur, Munawir; Rahmawati, Rahmawati (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
Community participation in tourism development is mainly related to forms of community participation, community motivation and the impacts of tourism development on local communities that need to be further optimized, with the basic premise that it is an effort to develop tourism by referring to the concept of community-based tourism development. The aim of this research is to describe the characteristics of creative economic tourism development that is based on active community participation so that it can increase Regional Original Income. This research uses a qualitative approach. The sampling technique was snowball sampling technique. The research population is the entire community in the South Konawe Regency area. Meanwhile, the sample taken as the main data source is people who actively carry out participation activities in the creative economy sector. The data collection techniques used were observation and interviews. Data collected from research results in the field were then analyzed descriptively qualitatively. The research results show that there is a link between Regional Original Income (PAD) and creative economic tourism, namely the presence of a new economic form that can become a source of the community's economy. If this is developed more professionally, it will become a new source of PAD for the South Konawe Regency government. The development of creative economic tourism based on local community participation has not run optimally, where the development of creative economic tourism still receives very little attention from the local government, especially the role of the government as a facilitator to provide facilities that are needed by creative economic actors, including training for actors to improve quality and productivity, providing production equipment for business actors, and assistance in accessing capital.